Cadeia produtiva do leite em Itabi/SE : entraves e oportunidades - Carpejani, Eduardo (2004)
The Chain Productive is important for the sources economic, social and ambient of the sustainable development. In this study, the same one was the tracks of from the definition of the citizens of the process and the analysis of its functioning, evaluating its relevance through the determination of the impediments and chances that intervene with its process. Each time more, the success of the agricultural enterprise depends on the success of all its productive chain. In a global economy, the producer is affected directly by the degree of organization of the world-wide market in which it is inserted. The efficiency of the integrated chain not only depends on the efficiency of production in each segment, but mainly of the efficiency of the flow of information that when adjusted, they allow to reduce costs of transactions, either in the control of the production, either in the aspects of logistic and quality. The example of other Regions northeast, the milk production in Sergipe is intent in the half region half-barren, and provide, mainly, of small explorations of family-mercantile base, consisting, over all, in strong factor of economic sustentation of the small properties. The climatic inconsistency of this region, allied to the extreme agrarian spalling and the limited natural resources and of capital, they configure, however, a picture of intermittent instability of agroecosystem there predominant, still sufficiently devoid, among others basic actions, of a hidric and agrossilvipastoril infrastructure capable to assure its sustentainment. The confrontation of this challenge, it passes not only, for politician-institution measures of collective reach, but also for the incorporation of predominant adjusted technological innovations to agroecosystem, that they make possible its development in competitive and sustainable bases, emphasizing alimentary systems of low cost and limited use of insumos. Of this form, given the relevance of the creation of milk cattle for the small land proprietors and consequently for the development of cities with the similar characteristics to the ones of Itabi/SE, this work aims at to identify to the impediments and the chances that influence in the partner-economic growth and the ambient balance of this region, through the evaluation of the Productive Chain of Milk in this city of the half-barren sergipano, contributing for the reduction of the place process of insustentabilidade. With the objective to characterize the productive chain of milk, in this work, we identify specifically, the corridor of commercialization used for the creators of the region with the purpose of: To trace strategies that assist in the management of bovine milk aiming at a sustainable development of the city; To optimize the use of the existing and available natural resources in the region; Oportune the lasting permanence and the consequent sustentation of the inhabitants of Itabi/IF. Moreover, we analyze the impediments and the chances, ahead of the importance of this product for the partner-economic growth of the region, through: Public politics for the fortify and structure of the Productive Chain of Milk; Stimulaton to the creation of new products, contributing for economic development e; Improvement of the educational level. Therefore, the choice of the Productive Chain of the Milk as white of this study if must to the partner-economic importance of the sector for Sergipe as generating source of jobs and supplier of a product of great importance for the feeding human being, agricultural how much in such a way urban, besides mainly promoting the balance and the sustentation for the economy of the small producer.